Preface - Saxena, Vinod P.; Sharma, Leena (Communications in Mathematics and Applications, 2023)
Preface It is a great privilege for us to present the proceedings of the 9th International Conference of Gwalior Academy of Mathematical Sciences 2022, held at Pimpri Chinchwad College of Engineering, Pune, Maharashtra, India during 29th September to 2nd October 2022 as a special issue entitled “Recent Trends in Mathematics and Applications” in the Communications in Mathematics and Applications. We hope that you will find it useful, exciting and inspiring. Mathematics is an ever-evolving field, with applications that extend across multipledisciplines, from engineering and physics to economics and computer science. The synergy between pure and applied mathematics has paved the way for numerous breakthroughs and innovations. This conference served as a platform to bridge the gap between these two facets of mathematics, fostering a rich exchange of ideas and knowledge. The papers included in these proceedings reflect the diversity and depth of mathematical research showcased during the conference. They delve into a wide spectrum of topics, from abstract theories to real-world problem-solving. The research presented here is a testament to the collective efforts of mathematicians who are pushing the boundaries of human understanding. We would like to extend our heartfelt gratitude to all the participants, authors, reviewers, and organizers who contributed to the success of this conference. Your dedication and passion for mathematics have been instrumental in creating a vibrant and stimulating environment for intellectual exchange. We hope that these proceedings serve as a valuable resource for researchers, students, and enthusiasts alike, inspiring further exploration and collaboration in the fascinating world of mathematics. We also record our thanks to RGN Publications and its editorial staff for their sincere cooperation in the publication of this proceedings.